Analisis Pelaksanaan Pembiayaan Multiguna pada Bank Syariah Indonesia KC Medan S. Parman - Muhammad Iqbal Pane; Ahmad Amin Dalimunthe (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This exploration is roused by the elements of the elements of the Indonesian economy, in light of the fact that after the money related emergency in 1998, banking execution became poor. After the emergency, the financial exhibition showed advancements. Then, at that point, came the PT. Bank Syariah Indonesia KC Medan S. Parman which gives multipurpose financing items, specifically purchaser financing without guarantee. On a basic level, acquiring unstable financing dispensed by banks requires a troublesome interaction, however it is different with PT. Bank Syariah Indonesia KC Medan S. Parman which is progressively being visited by clients who will apply for multipurpose financing after the financing is sent off and everything is fruitful. The motivation behind this examination is to execute the depiction of multipurpose financing that can give accommodation to clients. This examination utilizes subjective exploration with distinct methodology with the meeting technique, which investigates information by gathering, summing up and choosing things in regards to multipurpose financing. after that it is introduced as a stream visit (outline of connections among classes) and afterward ends can be drawn about regardless of whether the execution of multipurpose financing gives comfort to clients. The aftereffects of this study show that the most common way of executing multipurpose financing incorporates : multipurpose financing applications, MOU (Notice of Understanding) arrangements, financing council endorsements, contract endorsements, endorsements and endorsements did independently and all things considered. In compiling this research, the researcher chose to conduct qualitative research with data collection methods through field observations and also existing literature. PT. Sharia Bank KC Medan S. Parman, it was concluded that the composition and human resources were carried out effectively. It can be seen the implementation of Multipurpose Financing at PT. Bank Syariah Indonesia KC Medan S. Parman through its simple needs so that the implementation of this multipurpose financing provides accommodation, comfort and convenience to customers. Keywords: Multipurpose Financin, Islamic Bank